Assessment of androgen receptor, IGF-IR and insulin receptor expression in male patients with severe peripheral artery disease. Issue 1 (January 2022) - Andreucci, Michele; Rigiracciolo, Damiano Cosimo; Bracale, Umberto Marcello; Ielapi, Nicola; Provenzano, Michele; D'Iuorno, Diletta; Michael, Ashour; Mastroroberto, Pasquale; Serraino, Giuseppe Filiberto; Maggiolini, Marcello; Serra, Raffaele
Abstract: Background: Peripheral artery disease (PAD) of the lower limbs is a common condition that can affect quality of life. Androgen receptor (AR) can exert sex-specific effects on metabolic system, endothelial function and vascular tone. IGF-I receptor (IGF-IR) and insulin receptor (IR) may also be involved in the aforementioned functions. The aim of this study was to evaluate AR, IGF-IR and IR expression in the arterial vessel walls of PAD patients. Results: This is a cross-sectional study examining 30 males with PAD undergoing open surgery procedures. Mean age was 75.9 ± 8.8y. All patients belonged to Rutherford stage 4–6. Median expression levels of IR, IGF-IR and AR significantly decreased from stage 4–6 (p < 0.05). Significance: The study evidenced a progressive decrease of IR, IGF-IR and AR expression as the severity of disease increased. Altered levels of IR, IGF-IR and AR following PAD may be useful for the clinical evaluation of these patients. Abstract : Peripheral artery disease; IGF-I receptor; Insulin receptor; Androgen receptor; PAD; AR; IGF-IR; IR.